A Brachypodium UDP-Glycosyltransferase Confers Root Tolerance to Deoxynivalenol and Resistance to Fusarium Infection - Pasquet, Jean-Claude (Plant Physiol, 2016)
Fusarium head blight (FHB) is a cereal disease caused by Fusarium graminearum, a fungus able to produce type B trichothecenes on cereals, including deoxynivalenol (DON), which is harmful for humans and animals. Resistance to FHB is quantitative, and the mechanisms underlying resistance are poorly understood. Resistance has been related to the ability to conjugate DON into a glucosylated form, deoxynivalenol-3-O-glucose (D3G), by secondary metabolism UDP-glucosyltransferases (UGTs). However, functional analyses have never been performed within a single host species. Here, using the model cereal species Brachypodium distachyon, we show that the Bradi5g03300 UGT converts DON into D3G in planta. We present evidence that a mutation in Bradi5g03300 increases root sensitivity to DON and the susceptibility of spikes to F. graminearum, while overexpression confers increased root tolerance to the mycotoxin and spike resistance to the fungus. The dynamics of expression and conjugation suggest that the speed of DON conjugation rather than the increase of D3G per se is a critical factor explaining the higher resistance of the overexpressing lines. A detached glumes assay showed that overexpression but not mutation of the Bradi5g03300 gene alters primary infection by F. graminearum, highlighting the involvement of DON in early steps of infection. Together, these results indicate that early and efficient UGT-mediated conjugation of DON is necessary and sufficient to establish resistance to primary infection by F. graminearum and highlight a novel strategy to promote FHB resistance in cereals.